Low incidence of Pneumocystis jirovecii pneumonia in an unprophylaxed liver transplant cohort. Issue 5 (11th August 2013) - Sarwar, S.; Carey, B.; Hegarty, J.E.; McCormick, P.A.
Abstract: Background: Liver transplant recipients are managed with a range of immunosuppressive regimens that place them at heightened risk of life‐threatening opportunistic infections such as Pneumocystis jirovecii pneumonia (PJP). No routine PJP prophylaxis is used at out institution. We reviewed the incidence of PJP in this cohort of unprophylaxed liver transplant recipients. Methods: We examined all liver transplants performed between January 2000 and January 2012 in Ireland's National Liver Transplant Centre, St. Vincent's University Hospital, Dublin. Cases were identified through a computerized database and through the histopathology and microbiology registration system. The diagnosis of PJP was confirmed by identification of Pneumocystis cysts in bronchoalveolar lavage (BAL) fluid or on autopsy specimens using Grocott–Gomori methenamine‐silver nitrate or modified Wright–Giemsa staining methods. Results: During the study period, 687 liver transplants were performed. We found 7 cases of PJP with an incidence rate of 0.84 per 1000 person transplant years. Five cases occurred within 12 months of transplant with 2 cases occurring at 56 and 60 months, respectively. Two cases were diagnosed at postmortem; 1 previously had negative cytology from BAL, while the other could not be bronchoscoped because of rapid deterioration in the clinical condition. Three of the 5 treated patients died. Conclusions: The incidence of PJP in this cohort was very low, but the case fatality rate was high. Two cases occurred well after the usual recommended period of prophylaxis. In institutions with a very low risk of infection, targeted rather than universal prophylaxis may be reasonable.